An Empirical Study of Graduates’ Attributes, Graduates’ Skills, Job Mismatch, and Unrealistic Salaries as Unemployment Factors Among Malaysian Graduates - Jeffri, Nur Fatin Izzati; Abdul Rahim, Ramita (Advances in Social Sciences Research Journal, 2023)
Malaysian graduates today face challenges and struggles in the employment market. For the past few years, the unemployment problem has gotten worse. The rising unemployment rate is a serious issue since it could harm Malaysia's educational system's reputation and, as a result, cause some employers to lack confidence in the capabilities of our local graduates. Malaysian universities produce a large number of graduates, but an amazingly small percentage of those graduates find gainful employment. This problem develops when graduates seek to succeed in their academic achievements rather than practicing and cultivating traits within themselves. Employers today prefer graduates with working experience. Graduates who are selective about getting a job with a high salary do not fit the requirements for employment. So, it is crucial to address the issue's underlying cause immediately. This study is to determine the relationship between graduates’ attributes, graduates’ skills, job mismatch, unrealistic salaries, and unemployment among Malaysian graduates. This study used a self-administered questionnaire that was distributed among alumni of a public university. The sampling technique used was purposive sampling. The sample size was determined by G*Power analysis. Data was analyzed by multiple regression analysis using SPSS version 26.0 as a tool to examine the relationship for each variable. The findings of this study reveal that there is a positive relationship between the four factors that contribute to unemployment among Malaysians, and the most important factor contributing to unemployment is graduates’ attributes. The findings have suggested significant factors to improve for graduates, parents, a body of government, education institutions, as well as the industry sector.